Voice mimicry exhibited by Grey-sided Laughingthrush Garrulax caerulatus (Hodgson, 1836) in Phulchoki Mountain, an important bird area, central Nepal - Baral, Hem Sagar (Our Nature, 2019)
This paper informs Grey-sided Laughingthrush voice mimicking behaviour recorded at different places and different situations within thick forests, similar to other voice mimicking bird species.